(untitled) (Third Sector Social Economic Review, 2023)
Broken windows cause crime, affect people’s attitudes towards that place, and cause more problems. The aim of this study is to examine the effect of organizational broken windows on counterproductive work behaviors. Data were obtained from 252 employees working in Sivas State Hospital by online survey technique. In the analysis of the data, explanatory factor analysis, descriptive statistics, Pearson correlation, and linear and multiple regression analyses were used. It was determined that the individual broken windows and managerial broken windows dimensions of organizational broken windows were positively related to counterproductive work behaviors. It was determined that the organizational broken windows scale and managerial broken windows dimension positively affected counterproductive work behaviors. On the other hand, it was determined that individual broken windows size had no effect on counterproductive work behaviors. Managerial broken windows, unethical behavior, or managerial practices that disrupt the order in the organization, increase counterproductive work behaviors. Unlike other studies, the findings of this study showed that not only physical conditions but also management practices are effective in broken windows. Petty things can cause severe crimes and consequences, creating a butterfly effect within the system. Timely solutions should be produced to prevent more serious crimes from being committed in organizations, managerial disorders must be resolved.